2013
DOI: 10.1155/2013/102901
|View full text |Cite
|
Sign up to set email alerts
|

Rhinacanthus nasutusImproves the Levels of Liver Carbohydrate, Protein, Glycogen, and Liver Markers in Streptozotocin-Induced Diabetic Rats

Abstract: The present study was designed to investigate the total carbohydrate, total protein, and glycogen levels in the liver and to measure functional liver markers such as aspartate aminotransferase (AST) and alanine aminotransferase (ALT) in streptozotocin-(STZ-) induced diabetic rats after treatment with methanolic extract of Rhinacanthus nasutus (R. nasutus). The methanolic extract of R. nasutus was orally administered at 200 mg/kg/day while glibenclamide was administered at 50 mg/kg/day. All animals were treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Meanwhile, the biochemical indices such as enzymes found in the liver and kidneys are useful markers for assessment of tissue damage [ 39 ]. Tissue enzymes can also indicate tissue cellular damage caused by chemical compounds before structural damage that can be detected by conventional histological techniques [ 40 ]. The observation showed that liver enzymes such as ALP, AST, and ALT were significantly higher in HFD and HFDO groups ( Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the biochemical indices such as enzymes found in the liver and kidneys are useful markers for assessment of tissue damage [ 39 ]. Tissue enzymes can also indicate tissue cellular damage caused by chemical compounds before structural damage that can be detected by conventional histological techniques [ 40 ]. The observation showed that liver enzymes such as ALP, AST, and ALT were significantly higher in HFD and HFDO groups ( Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…In previous reports, methanol was reported as a suitable solvent for isolating the active components from R. nasutus (Rao et al, 2013). Brimson et al (2011) has shown that the root extract of R. nasutus prevented the hyotoxic conditions from HT-22 cell death by reducing the production of reactive oxygen species (ROS).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that hyperglycemia is commonly associated with disturbance of lipid metabolism, leading to the increased TC and low-density lipoprotein as well as decreased high-density lipoprotein levels [6, 29–32]. The elevated levels of TC and LDL could be risk factors for cardiovascular disease; conversely, the increased HDL levels, which play a key role in cholesterol transport from the periphery to the liver, reduce the risk of cardiovascular disease [6, 32].…”
Section: Discussionmentioning
confidence: 99%